2014
DOI: 10.1007/s00167-014-3462-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of anatomic single- and double-bundle anterior cruciate ligament reconstruction techniques using the quadriceps tendon

Abstract: DB ACL reconstruction using quadriceps tendon can restore biomechanics of the knee to that of the intact ACL regardless of whether three or four tunnels are used, but SB reconstruction does not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…The MM posterior shift is probably associated with losing the meniscal function as a secondary stabiliser. ACL reconstruction is well known to be effective in repressing abnormal anterior tibial translation [14,16]. In addition, some biomechanical studies demonstrated that ACL reconstructions could change the contact areas and pressures of the tibiofemoral joint postoperatively [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…The MM posterior shift is probably associated with losing the meniscal function as a secondary stabiliser. ACL reconstruction is well known to be effective in repressing abnormal anterior tibial translation [14,16]. In addition, some biomechanical studies demonstrated that ACL reconstructions could change the contact areas and pressures of the tibiofemoral joint postoperatively [11,22].…”
Section: Discussionmentioning
confidence: 99%
“…Three‐dimensional evaluation of joint stability is a contemporary method to evaluate joint kinematics for purposes of diagnosis and treatment efficacy . It is also important to assess joint stability under conditions intended to replicate joint dynamics during the normal step cycle as exemplified by quantification of angular displacement during application of translational force to the tibia performed in this investigation . Techniques used to quantify rotation and translation in this study have been previously validated in the canine stifle .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of eliminating abnormal tibial translation and rotation following CrCL graft reconstruction is a perpetual challenge of orthopedic surgery since joint instability is strongly associated with progressive joint disease . Suture elongation can lead to canine stifle instability following extracapsular stabilization, joint rotational stability is not fully restored by current extra‐articular and osteotomy techniques, and contemporary extra‐articular prosthetic stabilizations do not result in normal joint kinematics despite acceptable functional outcomes .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a biomechanical standpoint, tensile tests demonstrated that cross-sectional area of the quadriceps tendon graft was nearly twice that of the bone-patellabone graft with ultimate load to failure, and stiffness was also significantly higher for the QT graft. Recent in vitro study demonstrated quadriceps tendon to restore native kinematics to an ACL-deficient knee, with double-bundle quadriceps tendon restoring in situ ACL graft forces to more similar than that of the intact ACL [74].…”
Section: The Restoration Of Knee Kinematics; Individualized Acl Surgerymentioning
confidence: 99%